PENINGKATAN HASIL BELAJAR GERAK DASAR PERMAINAN KIPPERS MELALUI MODIFIKASI ALAT PEMBELAJARAN - Irsan Rifai; Agus Kristyanto (PHEDHERAL, 2017)
The purpose of this research was to improve the study result of basic movement in kippers on students in class 4B Bratan 1 State Elementary School No.71 Surakarta school year 2016/2017.This research was a Class Action Research. This research was done in two cycles, with each cycle contains planning, implementation, observation, and reflection. The subjects of this research were 36 students in class 4B Bratan 1 State Elementary School No.71 Surakarta. The sources of data were from teachers, students, and researchers. The techniques of collecting data were observation, test. The validity of the data used data triangle technique. The technique of analyzing the data used descriptive technique which based on the quantitative analysis with percentage.From the analysis, the result obtained from pre-cycle to cycle I and from cycle I to cycle II. This was observed from the study result of the students on pre-cycle. From 36 students, it was only 12 students who passed and 24 students who failed or with percentage 33,3% of students who pass and 66,7% of students who failed. Then the study result which was shown by students from cycle I showed the improvement of 20 students or 55,6% who passed and 16 students or 44,4% who failed. In cycle II, the improvement of the study result was 86,1% or 31 students who passed and 13,9% or 5 students who failed.The conclusion of this research was using the modification of education tool could improve the study result of basic movement in kippers game on students in class 4B Bratan 1 State Elementary School No.71 Surakarta school year 2016/2017.